Preoperative factors predicting saphenous vein graft occlusion in coronary artery bypass grafting: a multivariate analysis. - Malinska, Agnieszka; Podemska, Zuzanna; Perek, Bartlomiej; Jemielity, Marek; Buczkowski, Piotr; Grzymislawska, Malgorzata; Sujka-Kordowska, Patrycja; Nowicki, Michal (Histochemistry & Cell Biology, 2017)
Saphenous vein segments are frequently used as aortocoronary bypass grafts, particularly in patients over 65 years of age. In the majority of patients, venous grafts maintain their patency for 5-6 years; however, some become occluded within 12 months after surgery. There are some defined predictive biological factors used to assess saphenous vein graft long-term patency rates, but little is known about molecular parameters for estimating the risk of early vein occlusion. The pathogenesis of this process involves the proliferation of stem cells, as well as progenitor cells, in the graft wall. Histologically, this is reflected by CD34 and CD133 expression in endothelial and smooth muscle cells. Thus, the aim of present work was to perform a multivariate analysis of stem cell and progenitor cell markers in saphenous vein graft walls before transplantation to arterial circulation and correlate these results with early graft occlusion. A total of 718 patients, who underwent coronary artery bypass grafting using a saphenous vein graft, were enrolled in this prospective study. CD34, CD133 and von Willebrand factor expression was evaluated via immunohistochemistry. A multivariate analysis revealed that strong CD133 expression in smooth muscle cells can be considered a risk factor for early graft failure. Our findings suggest that CD133 expression in smooth muscle cells of the tunica media in saphenous vein grafts obtained from coronary artery bypass graft patients before graft transplantation to coronary circulation might predict the possibility of early graft occlusion.